Understanding comparative politics : a framework for analysis - Kamrava, Mehran, 1964- (Routledge, 2008)
Comparative politics has undergone significant theoretical changes in recent decades. Particularly since the 1980s, a new generation of scholars have revamped and rejuvinated the study of the subject. Mehran Kamrava examines current and past approaches to the study of comparative politics and proposes a new framework for analysis. This is achieved through a comparative examination of state and social institutions, the interactions that occur between them, and the poltical cultures within which they operate. The book also offers a concise and detailed synthesis of existing comparative frameworks that, up to now at least, have encountered analytical shortcomings on their own.